Plate VIII: Chlorophyceæ - Whipple, George Chandler (The Microscopy of Drinking Water, 1914)
Illustrated plate depicting various forms of chlorophyceæ (green algae), microscopic plant organisms living in water. The magnification of the organisms depicted on the plate is 250 diameters.
Keywords: Scientific illustration; Microscopy; Microorganisms; Green algae; Water--Analysis